2006
DOI: 10.1016/j.jbtep.2006.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Do children with obesity implicitly identify with sedentariness and fat food?

Abstract: We investigated whether youngsters with obesity (n ¼ 39) differed from a control group (n ¼ 39) in their self-reported attitudes towards and in their implicit identification with physical activity and food. Self-reported attitudes were assessed using a rating scale; implicit identification was assessed using a self-concept Implicit Association Task (IAT). Results revealed a marked group difference on the implicit identification with food: Only youngsters without obesity identified themselves more with non-fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
2
13
0
2
Order By: Relevance
“…No such findings have ever been obtained when food wanting (Experiment 1) or the tendency to associate one's self (Craeynest et al, 2006) or other valenced stimuli with different types of food were assessed. Although obese and normal-weight individuals have been shown to differ in their automatic evaluations of savory and sweet unhealthy foods (Czyzewska & Graham, 2008), this is the first instance where differences in how those same groups respond to healthy and unhealthy foods have been observed.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…No such findings have ever been obtained when food wanting (Experiment 1) or the tendency to associate one's self (Craeynest et al, 2006) or other valenced stimuli with different types of food were assessed. Although obese and normal-weight individuals have been shown to differ in their automatic evaluations of savory and sweet unhealthy foods (Czyzewska & Graham, 2008), this is the first instance where differences in how those same groups respond to healthy and unhealthy foods have been observed.…”
Section: Methodsmentioning
confidence: 93%
“…The second factor concerns the manner in which automatic food cognition is typically assessed. Previous studies have relied on the IAT, EAST and AP tasks which require participants to categorize foods with either the self (Craeynest et al, 2006) or valenced stimuli ). Yet even greater diagnostic and predictive information about food-choice may be obtained when we consider how people automatically relate rather than simply categorize food stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that overweight 12–18 y olds showed better memory for food vs. control words imbedded in a grid, although there was no evidence for attentional interference in the overweight group as measured by the number of food vs. control words initially identified [10]. A study using a self-concept Implicit Association Task, in which participants had to categorize words or pictures as fat vs. non-fat and self vs. other, found that 9–18 y olds who were lean, but not those who were obese, were quicker to respond when `non-fat' and `self' categorizations required the same key press; the authors suggest this might indicate a greater self-identification with healthy than unhealthy foods among the lean children [11]. Another study found that overweight 6–11 y olds showed increased lip sucking in response to high energy food pictures and food odors, and were more likely to classify non-food odors as food odors during the pre-prandial state, suggesting a number of potential orofacial indicators of food cue responsiveness [12].…”
Section: Measuring Weight-related Appetitive Traits In Childhoodmentioning
confidence: 99%
“…It has been argued that the IAT is affected less by social desirability and measures other, more automatic, aspects of associations than questionnaires. The task has been used in a wide variety of domains, including obesity research (e.g., Craeynest, Crombez, De Houwer, Deforche, & De Bourdeaudhuij, 2006, 2007Roefs & Jansen, 2002). Interestingly, until now, IAT studies failed to find different valence associations for highfat food vs. healthy food in overweight and obesity compared with lean controls (see Roefs & Jansen, 2002;Craeynest, Crombez, Haerens, & De Bourdeaudhuij, 2007).…”
Section: Introductionmentioning
confidence: 99%